Technological training - education for industry - Alexander, D. H. (Statistical and Social Inquiry Society of Ireland, 1957)
The invention of the steam engine and the widespread use of machinery m the rapidly growing manufacturing industries of the last century created the demand for a new form of training for those whose business it was to design, make and operate the new machinery. The rate of change was so rapid that it no longer gave the craftsman time to develop the forms and methods of construction by the time consuming process of trial and error. The sciences of geometry, applied mechanics and physics had to be brought to the aid of the mechanic to accelerate the speed of engineering development and avoid the delays caused by traditional methods. The young mechanic sought instruction from the scholar and it is interesting to note the number of clergymen whose ability in mathematics led to their interesting themselves in the new developments.
Read before the Society in Belfast, on January 25th 1957
Keywords: Technological training; Education; Technological change; 314.15